PENERAPAN GCG DAN DAMPAKNYA PADA CSR (PERUSAHAAN PEMENANG IIGC – ASEAN CG SCORECARD) - Ririn Breliastiti; Sucinda Putri; Silwy Valentina (Universitas Bunda Mulia, 2020)
Indonesia is ranked among the lowest in corporate governance in Southeast Asia. The better the application of CG is expected to be the better the company's CSR disclosure. In the digital age, a company's website is one source of information that can be used by companies to report and disclose CSR activities. This study aims to obtain empirical evidence regarding whether the implementation of GCG will impact the company's ability to disclose its CSR activities on the official website. This research is a comparative causal study, which the independent variable (X) is GCG and the dependent variable (Y) is CSR. Information on the company's annual financial statements is obtained from www.idx.co.id, while data on award-winning companies provided by IICG were obtained from SWA Magazine. The results of the study show that GCG has not been proven to have an impact on the disclosure of CSR activities on the website. Indications are that the organs in GCG function more to protect the interests of shareholders. In the realm of CSR, the role of this GCG organ has not been specifically regulated. CSR is an embodiment of GCG principles, namely responsibility and transparency of information. Companies that are committed to carrying out CG properly and consistently should realize these principles in CSR activities and report/ disclose these CSR activities through the official website. Companies that have been awarded as Indonesia Most Trusted Companies should be an example or benchmark for other companies. For this reason, seriousness, seriousness and commitment are needed, especially from the Chief Executive Officer (CEO) in running GCG. Keywords: GCG, CSR, IIGC, website